Nitrogen topdressing and application ways of fluazifop-p-butyl plus fomesafen in weed control and agronomic performance of common bean - Silva, Matheus G.; Arp, Orivaldo [UNESP]; Teodoro, Paulo E. (Acad Brasileira De Ciencias, 2015)
The objective of this study was to investigate the effect of interaction between nitrogen topdressing and different application ways (active ingredients) a.i. fluazifop-p-butyl + fomesafen in weed control and agronomic performance of common bean. The experiment was conducted during winter 2003 in Selviria/MS. The experimental design used was a randomized block design with four replications in a factorial scheme 2x7. The first factor was composed by the absence or presence of nitrogen topdressing, while the second factor consisted of different application ways of fluazifop-p-butyl + fomesafen. The following variables were measured: leaf N content, dry matter of plants, yield components (number of pods plant(-1), number of grains plant(-1), the average number of grains pod(-1) and mass of 100 grains), grain yield, phytotoxicity and weed control percentage. The nitrogen topdressing with 75 kg ha(-1) provided higher dry matter of plants, higher weed control and higher common bean yield of irrigated winter. In the absence of nitrogen topdressing in the application of urea before or together to fluazifop-p-butyl + fomesafen increased their effectiveness in controlling weeds without interference in the agronomic performance of common bean.
Keywords: nitrogen fertilization; herbicide mixture; Phaseolus vulgaris L.; urea